A CASE SERIES OF DHAT SYNDROME AND THE EFFICACY OF PROTHIADEN(DOSULEPIN) IN MANAGEMENT - T, SHRUTHI; PARTHIBAN, KAVITHA; SELVAMANI, INIYAN; NAMBI, SHANTHI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Introduction: distressing beliefs about semen loss leading to physical and psychological consequences. The syndrome involves symptoms such as weakness, fatigue, anxiety, and depression, profoundly impacting daily life. Cultural beliefs and stigma surrounding semen loss exacerbate these symptoms, necessitating culturally sensitive treatment approaches. Methodology: This study examined the efficacy of Prothiaden (Dosulepin), a tricyclic antidepressant, in managing Dhat syndrome. A case series of ten adult male patients diagnosed with Dhat syndrome using ICD-10 criteria was conducted. Patients were treated with Prothiaden, starting at 50 mg and increasing to 100 mg over six weeks. Symptom severity was assessed using the Dhat Syndrome Evaluation Questionnaire at baseline and after six weeks. Data were analyzed using paired t-tests to compare pre- and post-treatment scores. Results: Treatment with Prothiaden resulted in significant reductions in symptom severity. Mean pre-treatment scores for worry about semen loss, anxiety, and somatic complaints were 7.2, 6.5, and 8.0, respectively. Post-treatment scores significantly decreased to 3.8, 4.0, and 5.2, respectively (p < 0.01 for all), indicating substantial improvements in both psychological and somatic symptoms. Conclusion: Prothiaden demonstrated significant efficacy in reducing the psychological and somatic symptoms of Dhat syndrome. The treatment not only addressed the cultural and psychosomatic dimensions of the disorder but also improved patients' overall well-being. These findings suggest that Prothiaden is a promising therapeutic option for Dhat syndrome, especially when combined with culturally sensitive psychosocial interventions.